Polydopamine-wrapped carbon nanotubes to improve the corrosion barrier of polyurethane coating. Issue 42 (29th June 2018) - Cai, Guangyi; Hou, Jian; Jiang, Dan; Dong, Zehua
Abstract : Nanocomposite reinforced polyurethane (PU) coatings have been prepared by an ultrasonication method with polydopamine-wrapped carbon nanotubes (PDA@CNTs) as the nanofiller. Abstract : Nanocomposite reinforced polyurethane (PU) coatings have been prepared by an ultrasonication method with polydopamine-wrapped carbon nanotubes (PDA@CNTs) as the nanofiller. The influence of the PDA@CNTs enhanced PU coating on the corrosion resistance and adhesion strength to Al-alloy was investigated by electrochemical impedance spectroscopy and the pull-off test during cyclic ageing tests, including the salt spraying test, UV irradiation and solution immersion. A comparison of the pristine PU against CNTs modified PU coatings revealed that the higher CNTs loading (2.0 wt%) increased the heterogeneity and porosity of PU, which could deteriorate the corrosion barrier of PU due to the poor dispersity, even though it also increased the adhesion strength of PU. In contrast, the PDA wrapped CNTs could improve the dispersibility of the CNTs in the PU matrix thanks to the greater compatibility of PDA with PU compared to CNTs. Further experiments indicated that increasing the PDA@CNTs loading could improve the adhesion strength, but and also increase the corrosion resistance of the PU coating to 10 7 Ω cm 2 even after 7 cycles of ageing tests. Morphological observations indicated that the PDA@CNTs could increase the compactness and decrease the defects of PU, preventing the initiation and propagation of micro-defects in the PU coating during long-term ageing tests.